2013
DOI: 10.1517/14656566.2013.775248
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment for infectious corneal ulcers

Abstract: Topical application with a broad-spectrum antimicrobial remains the preferred method for the pharmacological management of infectious corneal ulcers. Increasing reports of clinical failures and in vitro resistance to antibiotics to treat the most common infectious (bacterial) corneal ulcers are increasing concerns. New approaches for improvement in the pharmacological management of corneal ulcers should focus on strategies for a more rational and evidence-based use of current antimicrobials and development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 102 publications
0
28
0
1
Order By: Relevance
“…20,22 However, the AAO guidelines do state that combination fortified broad-spectrum antibiotic therapy should be considered for severe infections (i.e., central or severe ulcers or infiltrates .2 mm that are threatening the visual axis) and for ulcers unresponsive to initial treatment. 11,13 This study demonstrated that more than 56.2% of cornea specialists and 54.9% of general ophthalmologists use moxifloxacin to treat small or peripheral corneal ulcers. These findings are similar to that of Hsu et al,9 who demonstrated that the fourth-generation fluoroquinolones were the most popular antibiotic choice for bacterial keratitis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…20,22 However, the AAO guidelines do state that combination fortified broad-spectrum antibiotic therapy should be considered for severe infections (i.e., central or severe ulcers or infiltrates .2 mm that are threatening the visual axis) and for ulcers unresponsive to initial treatment. 11,13 This study demonstrated that more than 56.2% of cornea specialists and 54.9% of general ophthalmologists use moxifloxacin to treat small or peripheral corneal ulcers. These findings are similar to that of Hsu et al,9 who demonstrated that the fourth-generation fluoroquinolones were the most popular antibiotic choice for bacterial keratitis.…”
Section: Discussionmentioning
confidence: 85%
“…This is because no single class of antibiotics covers all of the causative microorganisms of bacterial keratitis and because bacterial resistance patterns are in a state of flux. 1,13 In general, monotherapy with a fluoroquinolone is usually sufficient for small or peripheral corneal ulcers, whereas dualfortified broad-spectrum antibiotics are recommended for larger or more severe corneal ulcers. 11,13 The advent of topical fluoroquinolone antibiotics in the 1990s 14 offered a way to treat corneal ulcers empirically with readily available prescription medication instead of using the more cumbersome fortified topical antibiotics.…”
mentioning
confidence: 99%
“…52 With regard to the treatment of bacterial corneal ulcers, topical fluoroquinolones are considered the drug of choice in the absence of microbiological evaluation. 56 A meta-analysis on the treatment of keratitis showed that when compared with combined fortified antibiotics such as aminoglycosides and cephalosporins, fluoroquinolones offer similar efficacy and a better tolerance profile. 51 However, as with bacterial conjunctivitis, increasing resistance to early-generation fluoroquinolones has been reported.…”
Section: Besifloxacin In Bacterial Keratitismentioning
confidence: 99%
“…Candida albicans is the most common yeast is more common in cold climates and often affects patients with pre-existing corneal disease or who have received longterm corticoid therapy [3]. Usually the treatment is very complex and presents a worse prognosis than visual bacterial keratitis, probably due to lack of effective [4] treatments. Conventionally the most commonly used in the treatment of fungal keratitis treatments have been polyenes concentrations that exceed a hundred times the minimum inhibitory concentrations and more frequent yeast but currently, is booming using the new azoles, these have not shown natamycin superiority to [5].…”
Section: Editorialmentioning
confidence: 99%